Practical high-fidelity frequency-domain force and location identification. (1st October 2015) - Ghaderi, Pooya; Dick, Andrew J.; Foley, Jason R.; Falbo, Gregory
Highlights: High fidelity scheme for impact force characterization is presented. Practical approach using local response behavior and a model of a segment of the structure. Identification scheme studied by using simulations and validated with experiments. Abstract: Identifying the force information and location of an impact event is important for predicting and/or monitoring potential damage to the structures. Directly measuring the impact event and/or locating the impact force is not always possible due to the nature of the impact or the structure. In this work, a new force and location identification method is introduced which utilizes a spectral finite element method (SFEM) model of the structure. The identification technique is demonstrated and studied through its application to beam structures in order to identify impulsive loads. Wave propagation data collected with accelerometers placed on the structure are used in order to determine the impact information. When the impact force is applied between the accelerometers, the calculated force is distributed over the two accelerometer positions on either side of the impact location. The location identification process uses the distribution of the identified force information in order to locate the impact position. This method is performed by matching simulated data to the identified force data by tuning the impact location within the numerical model. When a sufficient level of agreement is achieved, the impact location is determined. In order to validate the results of the numerical studies, identified impact forces and locations are calculated for experimental data and good agreement is observed with the measured force information and impact locations.